Virtual in real life (VIRL) - Neo, Daryl Jia Xun (Nanyang Technological University, 2023)
The Metaverse aims to provide a shared and open virtual environment where users can interact with one another using digital avatars through the usage of virtual reality technology. This includes socializing, playing games or even working together without the need for physical presence. Additionally, having social engagement in a VR setting can also help to reduce social anxiety by providing a controlled environment for people to practice social interactions and work on their social skills. This report showcases a Metaverse application which act as a platform for users to connect and form relationships within the virtual world to increase the potential for meetings in the real world.